If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2(x + -5) + 4x = -2 Reorder the terms: -2(-5 + x) + 4x = -2 (-5 * -2 + x * -2) + 4x = -2 (10 + -2x) + 4x = -2 Combine like terms: -2x + 4x = 2x 10 + 2x = -2 Solving 10 + 2x = -2 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-10' to each side of the equation. 10 + -10 + 2x = -2 + -10 Combine like terms: 10 + -10 = 0 0 + 2x = -2 + -10 2x = -2 + -10 Combine like terms: -2 + -10 = -12 2x = -12 Divide each side by '2'. x = -6 Simplifying x = -6
| 2s-5=10 | | 12x+43=6x+29 | | 6-0.75x=x | | 3x^2(2x^2-2)=(-x^2)(5x^2+2) | | 7=5c-3 | | t^2+4t-25=0 | | x-9x-4=-2x-2 | | 8.71+8.4p=-10.73+6.6p | | 0=-2x^2+x+1 | | z^3+3iz^2-3z-i=8i | | (7x-20)=(4x+16) | | 6y-3y-7=37.25 | | 9z+z=9z+8 | | z+14.7=18.2 | | (X+8)(x+11)=0 | | (4X-5Y)(2X+7Y)= | | z^3+3iz^2-3z-9i=0 | | y+13=23 | | 4(x-2)=10x-0 | | 3m-1=(-6) | | 4x-9=3(x-3) | | 9-c=17 | | 18.18+15.6t=-7.3t+20t-17.78 | | z+8=21 | | 14y=224 | | Y^2+18=6x | | 3x-2(y-5)=0 | | 3x^4-3x^2+1=0 | | 2(W+4)-3(W+4)=0 | | 6-z=-8 | | X^4-4*x^3+8x= | | y=x^2+1.5xfor-2 |